Samozaposleni, ekonomsko odvisne osebe in obstoj delovnega razmerja - Senčur Peček, Darja (Delavci in delodajalci, 2014)
The paper discusses the phenomenon of the growing number of self-employed persons and the reasons for such increase, as well as the categories of these self-employed and their legal status. It specifically deals with the category of economically dependent persons, both in the light of the Slovenian legislation compared to some foreign ones, as well as with the proposed European legislation. Attention is paid to the emergence of seemingly self-employed persons and the urgent need to take action against this phenomenon; in addition to that, solutions from other legal systems are presented.
Keywords: delovna razmerja; delovno pravo; samozaposlovanje